The Regenerationist artists in the Europa magazine - Giráldez Torres, Lucía (Escritura e Imagen, 2025)
Europe. Magazine of popular culture was an interesting magazine published in 1910 with an important artistic section, currently in oblivion. The aim of this article is to unravel the aesthetic and the historical artistic content of the gazettes dedicated to different artists of the Spanish Regenerationist environment, exposing the peculiar and profound relationship that existed between literature, philosophy and the plastic arts of the time.
Keywords: Regenerationism; Spanish painting; 20th century; Spanish Nationalism; literature; aesthetic